ANALYSIS ON THE FATIGUE FRACTURE CHARACTERISTICS OF COMPOSITE INSULATOR CORE ROD - ZHAO XinZe; XI SenMing; WANG Lei; PENG WenYu; ZHAO MeiYun (Jixie qiangdu)
In order to analyze the fatigue fracture surface characteristics of composite insulator core rod, the fatigue damage process of insulators under different amplitude/torsion angle conditions was simulated by dynamic load fatigue test. The surface morphology of insulator fracture was observed by using an super deep scene 3 D microscope, and combined with fatigue loads and the number of stress cycles, the formation mechanism of the fracture surface was analyzed. The fractal geometry theory was used to describe the complexity of the fracture morphology in quantitatively and discussed the relationship between the fractal dimension and the fatigue loads. The results show that the fatigue fracture process of core rod is actually a stress corrosion process, which means that under the action of stress, the crack of the fiber gradually deepens until it breaks. The deformation and abrasion caused by the cyclic stress all determined the fracture surface morphology. The fractal dimension of the fracture surface is between 2 and 3, and the linear regression correlation coefficient is above 0.99, the strong correlation shows that the fracture surface of the insulator has obvious fractal characteristics. The formation of the fracture surface is not only related to the deformation, but also related to the number of stress cycles. The fractal dimension of the fracture surface is positively correlated with the loads and negatively correlated with the number of load cycles.